Bridging The Digital Divide: A Comparative Study of Digital Competencies among TVET Teachers in TVET Institutions in Asian Countries - Ismail, Affero; , A., Ana; M., Muktiarni,; Sulaiman, Junita; Punyayodhin, Sulaganya; Feizi, Asghar (Journal of Technical Education and Training, 2025)
Digital competencies are very crucial in ensuring the successful of digital economy transformation and sustainability of the nation. To educate the new generation to become IT savvy, the teachers and instructors should have adequate knowledge and skills related to digital competencies. The study examines the digital competencies among teachers and instructors in selected TVET institutions in five countries namely Malaysia, Indonesia, Maldives, Thailand, and Iran. The research utilised descriptive statistics and ANOVA test to evaluate five important domains specified in the DigComp 2.0 framework. The five domains are Information and data literacy, Communication and collaboration, Digital content creation, Safety and Problem solving. The results indicate that there are generally high levels of competence with minor differences among institutes. There are no significant differences across institutes according to the ANOVA test with p=0.31. TVET institution in Indonesia consistently had the greatest scores, whereas TVET institutes in Thailand and Maldives consistently achieved lower scores across all components. Disparities may be ascribed to variables such as educational policy and infrastructure. The research highlights the need of customised digital literacy programmes, enhanced infrastructure, and cooperation among stakeholders to narrow the digital gap and provide graduates with the essential skills for the digital workplace.